Idiopathic Myointimal Hyperplasia of Mesenteric Veins of the Ileum and Colon in a Patient with Crohn’s Disease: A Case Report and Brief Review of the Literature - Sharon J. Song; Stuti G. Shroff (Case Reports in Pathology)
Idiopathic myointimal hyperplasia of the mesenteric veins (IMHMV) is a rare disease characterized by intimal smooth muscle proliferation, leading to the thickening of small to medium-sized mesenteric veins. This vascular disease mimics inflammatory bowel disease (IBD) clinically and endoscopically, while showing ischemic mucosal changes without the classic features of IBD on biopsy. Given the mixed picture, this entity is frequently misdiagnosed. Surgical resection of the diseased bowel segment reveals the true etiology of the pathology and is curative. We describe a case of a 59-year-old man with a long-standing history of Crohn’s disease refractory to medical therapy and status after multiple small bowel resections. The patient underwent a subtotal abdominal colectomy with pathology showing dense, indurated mesenteric adipose tissue, significant muscularis propria hypertrophy, and myointimal hyperplasia of the mesenteric veins in a peri-ileal and pericolic distribution, as confirmed by elastin stain. No evidence of mucosal ischemic changes or findings of chronicity or acuity were seen. IMHMV, a rare disease with a mixed presentation, poses a significant diagnostic challenge to clinicians and pathologists.